1991
DOI: 10.3904/kjim.1991.6.1.44
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary T-Cell Lymphoma of the Duodenum

Abstract: Primary malignant lymphoma located in the duodenum is a rarity. A case of primary lymphoma of the duodenum in a 27-year-old man, in which the 2 discrete masses of duodenal bulb and the second portion with pancreatic head invasion was found, is reported here. Immunohistochemical evaluation of the present case showed that lymphoma cells expressed the T-cell markers MT1 and UCHL1. Treatment consisted of pancreaticoduodenectomy followed by antineoplastic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…All NHLs are accounted for approximately 4% of all tumors arising in the GI system (2). The more lymphoid tissue is in parts of small intestine, the more incidence of lymphoma is depicted; thus, as expected, ileocecal region is the most frequent site, while the duodenum remains as the most infrequent site (3). Evidence of obstruction is secondary to rare form of intestinal lymphoma; duodenal primary lymphoma made our patient distinct.…”
Section: Introductionsupporting
confidence: 59%
“…All NHLs are accounted for approximately 4% of all tumors arising in the GI system (2). The more lymphoid tissue is in parts of small intestine, the more incidence of lymphoma is depicted; thus, as expected, ileocecal region is the most frequent site, while the duodenum remains as the most infrequent site (3). Evidence of obstruction is secondary to rare form of intestinal lymphoma; duodenal primary lymphoma made our patient distinct.…”
Section: Introductionsupporting
confidence: 59%
“…Enteropathy-associated T-cell lymphoma occurs commonly in the jejunum, either alone or in combination with multiple other sites in the gastrointestinal tract 1 ) . Although several cases of primary intestinal T-cell lymphomas were reported 7 , 8 ) , it has not been reported that the patient had extensive lymphoma lesions confirmed by biopsy throughout the entire gastrointestinal tract which is very rare in Korea.…”
Section: Discussionmentioning
confidence: 91%
“…[19][20][21][22][23][24][25][26][27][28][29] Higher grade tumors such as DLBCL had lower survival, 12,14,18,30,31 whereas T/NK-cell tumors, not observed in our series, accounted for the worst overall survival of 40 per cent at 1 year. 15,16,[32][33][34] Operations in our patients were required for significant tumor complications of bleeding or intestinal obstruction. The operations were complicated by technical challenges, recurrent bleeding, and postoperative sepsis.…”
Section: Discussionmentioning
confidence: 99%